Peruvian scientific production on Helicobacter pylori: a bibliometric analysis - Hernández-Vásquez, Akram (2020)
Objective: To evaluate the Peruvian scientific production on Helicobacter pylori. Materials and methods: Bibliometric analysis of original articles published until September 8, 2020, in journals indexed in PubMed, Scopus, Web of Science, LILACS, and SciELO. Bibliometric indicators were obtained. Likewise, analysis of the co-citation of authors and co-occurrence of terms with the terms included in the title and the abstract of publications was performed. Results: Data from 180 original articles were analyzed. An increase in the number of articles on H. pylori was found (R2 = 0.64, an average annual growth rate of 8.01%). A total of 777 authors were identified, with an average number of articles per author of 0.18, and a collaboration index of 5.64. The average number of citations per original article was 1.91. The Universidad Peruana Cayetano Heredia was the institution with the highest number of original articles (63.2%). The analysis of co-occurrence of terms found terms related to gastric cancer during the whole study period and, for recent years, terms related to the treatment of H. pylori infection and water sources. Conclusion: There is an increase in Peruvian production in original articles on H. pylori. In recent years, the study of the eradication of H. pylori and the transmission of the agent from water sources have been topics of interest.